The Modulation of Water, Nitrogen, and Phosphorous Supply for Growth Optimization of the Evergreen Shrubs Ammopiptanthus mongolicus for Revegetation Purpose - Roy, Rana; Mahboob, M. Golam; Arena, Carmen; Kader, Md. Abdul; Sultana, Shirin; Hasan, Ahmed Khairul; Wang, Jinxin; Sarker, Tanwne; Zhang, Ruiqi; Barmon, Milon (Frontiers in Plant Science, 2021)
Abstract Surface mining is a critical anthropogenic activity which significantly alters the ecosystem. Revegetation practices are largely utilized to compensate for these detrimental impacts of surface mining. In the present study we investigated the effects of five water (W) regimes (W40: 40%, W48: 48%, W60: 60%, W72: 72% and W80: 80% of field capacity), five nitrogen (N) (N0: 0, N24: 24, N60: 60, N96: 96 and N120: 120 mg kg‒1 soil) and five phosphorus (P) fertilizer doses (P0: 0, P36: 36, P90: 90, P144: 144 and P180: 180 mg kg‒1 soil) on morpho-physiological and biochemical parameters of Ammopiptanthus mongolicus plants to assess the capability of this species to be used for restoration purposes. The results showed that under low W-N resources, A. mongolicus exhibited poor growth performance (i.e., reduce plant height, stem diameter, and dry biomass) in coal-degraded spoils, indicating that A. mongolicus exhibited successful adaptive mechanisms by reducing its biomass production to survive a long in environmental stress conditions. Compared to control, moderate to high W and N-P application rates greatly enhanced net photosynthesis rates, transpiration rates, water use efficiency, chlorophyll (Chl) a, Chl b, total Chl and carotenoid contents. Under low-W content, the N-P fertilization enhanced the contents of proline and soluble sugar, as well as the activities of superoxide dismutase, catalase and peroxidase in leaf tissues, reducing the oxidative stress. Changes in plant growth and metabolism in W-shortage condition supplied with N-P fertilization may be an adaptive strategy which is essential for its conservation and restoration in desert ecosystem. The best growth performance was observed in plants under W supplements corresponding to 70% of field capacity, N and P doses of 33 and 36 mg kg‒1 soil, respectively. Our results provide useful information for revegetation and ecological restoration in coal-degraded arid degraded lands in the world using endangered species A. mongolicus.